Introduction to Sports Journalism - Zimmerman, Matthew; Burch, Lauren M.; Moritz, Brian (Human Kinetics, 2025)
"This book explores issues and challenges faced by modern sports journalists and provides practical insights related to the tools and knowledge required to succeed in this field"